2009
DOI: 10.1080/13548500903311554
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, engagement and resident physicians' self-reported errors

Abstract: Burnout is a work-related syndrome that may negatively affect more than just the resident physician. On the other hand, engagement has been shown to protect employees; it may also positively affect the patient care that the residents provide. Little is known about the relationship between residents' self-reported errors and burnout and engagement. In our national study that included all residents and physicians in The Netherlands, 2115 questionnaires were returned (response rate 41.1%). The residents reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
185
1
24

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(214 citation statements)
references
References 28 publications
3
185
1
24
Order By: Relevance
“…Unmarried physicians are expected to have a higher level of burnout due to younger age and a lack of family support. Similar results were found in a previous survey 29) that demonstrated that married physicians would experience less depersonalization. Highly educated physicians usually have more responsibility, stress and expectation for promotion, which can be a possible explanation for their high rate of burnout.…”
Section: Burnout and Its Association With Physicians' Sociodemographisupporting
confidence: 79%
“…Unmarried physicians are expected to have a higher level of burnout due to younger age and a lack of family support. Similar results were found in a previous survey 29) that demonstrated that married physicians would experience less depersonalization. Highly educated physicians usually have more responsibility, stress and expectation for promotion, which can be a possible explanation for their high rate of burnout.…”
Section: Burnout and Its Association With Physicians' Sociodemographisupporting
confidence: 79%
“…As previously mentioned, burnout is a significant mental health indicator because physicians with a high risk of burnout tend to have the intention to change jobs [17], be affected by job dissatisfaction [18] and provide low-quality patient care [19,20]. Among dentists, high job strain has a significantly higher odds ratio for burnout [39].…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 80%
“…Burnout is characterized by emotional exhaustion, depersonalization and negative self-evaluation among various professionals involved in people-oriented services, including health care staff such as physicians [15,16]. Physicians' burnout status has been reported to be associated with the intention to change jobs [17], job dissatisfaction [18] and low-quality patient care [19,20]. A review described burnout as more job-related and situation-specific than general IJOMEH 2014;27(6) 982 3.…”
Section: Participantsmentioning
confidence: 99%
“…SzĂĄmos vizsgĂĄlat jelzi, hogy az egĂ©szsĂ©gĂŒgyi dolgozĂłk kiĂ©gĂ©se nem az Ă©rintettek "magĂĄnĂŒgye": a burnout jelentƑs mĂ©rtĂ©kben befolyĂĄsolja a mƱhibĂĄk Ă©s a szövƑdmĂ©nyek elƑfordulĂĄsĂĄt [4,5]. E tĂ©mĂĄban talĂĄn a legnagyobb visszhangot kivĂĄltĂł kutatĂĄsi eredmĂ©nyt az American Journal of Infection Control 2012-ben publikĂĄlt közlemĂ©nye jelentette, amelyben a kutatĂłk 161 kĂłrhĂĄzban 7000 egĂ©szsĂ©gĂŒgyi dolgozĂł kiĂ©gĂ©sĂ©t vizsgĂĄltĂĄk.…”
unclassified